answersLogoWhite

0

4 x 3 x x 2 0?

User Avatar

Anonymous

15y ago
Updated: 4/28/2022

4x3=12x20=240

the answer to 4x3xx20 is 240

User Avatar

Wiki User

15y ago

Still curious? Ask our experts.

Chat with our AI personalities

JudyJudy
Simplicity is my specialty.
Chat with Judy
SteveSteve
Knowledge is a journey, you know? We'll get there.
Chat with Steve
MaxineMaxine
I respect you enough to keep it real.
Chat with Maxine

Add your answer:

Earn +20 pts
Q: 4 x 3 x x 2 0?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Algebra

How do you factor x squared plus x minus one half?

(x^2+x-1/2)= x(x+1)-1/2 [x + (1 - square root of 3)/2][x + (1 + square root of 3)/2] = 0 Check it: x^2 + x/2 + (square root of 3)x)/2 + x/2 + 1/4 + (square root of 3)/4 - (square root of 3)x/2 - (square root of 3)/4 - 3/4 = 0 x^2 + x/2 + x/2 + [(square root of 3)x]/2 - [(square root of 3)x]/2 + (square root of 3)/4 - (square root of 3)/4 + 1/4 - 3/4 = 0 x^2 + x - 2/4 = 0 x^2 + x - 1/2 = 0 How to find this roots: Using the completing the square method: x^2 + x - 1/2 = 0 x^2 + x = 1/2 x^2 + x + 1/4 = 1/2 + 1/4 (x + 1/2)^2 = 3/4 x + 1/2 = (plus & minus)(square root of 3/4) x = -1/2 + (square root of 3)/2 x = - 1/2 - (square root of 3)/2


Which two values of x are roots of the polynomial 3x2-3x plus 1?

let f(x) = 3x^2 - 3x + 1. The roots of f is the same as asking for x where f(x) = 0. So we do it f(x) = 0, 3x^2 - 3x + 1 = 0. Using "complete the square" method 3(x^2 - x) + 1 = 0 3(x^2 + (2 . - 1/2 . x) + (-1/2)^2 -(-1/2)^2) + 1 = 0 3(x - 1/2)^2 -3/4 + 1 = 0 3(x - 1/2)^2 + 1/4 = 0 By the quadratic formula, the solution comes out to be x = [3+√(-3)]/6 and x = [3-√(-3)]/6 or x = (3+i√3)/6 and x = (3-i√3)/6 in other words, the solutions are complex numbers.


X over 2 plus 3 equals 4?

-1


What is 2 430 090 in expanded form?

2,430,090 = (2 x 106) + (4 x 105) + (3 x 104) + (0 x 103) + (0 x 102) + (9 x 101) + (0 x 100) or (2 x 1000000) + (4 x 100000) + (3 x 10000) + (0 x 1000) + (0 x 100) + (9 x 10) + (0 x 1)


X2 - x - 6?

-4